Qualitative evaluation of the symptoms and quality of life impacts of long-chain fatty acid oxidation disorders. (January 2022) - Williams-Hall, Rebecca; Tinsley, Katie; Kruger, Eliza; Johnson, Chloe; Bowden, Alexandra; Cimms, Tricia; Gater, Adam
Background: Long-chain fatty acid oxidation disorders (LC-FAOD) are a group of rare autosomal-recessive genetic disorders characterized by metabolic deficiencies in which the body is unable to convert long-chain fatty acids into energy. To date, however, there is limited understanding of the patient experience of LC-FAOD. Methods: The symptoms, observable signs, and quality of life (QoL) impacts associated with LC-FAOD were explored via a focus group ( n = 8) and semi-structured interviews ( n = 6) with patients and caregivers of patients with LC-FAOD, and interviews ( n = 4) with expert clinicians. Data were analyzed via thematic analysis and summarized in a conceptual model. Results: Participants reported a wide range of signs and symptoms associated with LC-FAOD, broadly categorized as musculoskeletal, endocrine/nutritional/metabolic, neurological, gastrointestinal/digestive, sensory, cardiovascular, respiratory, urological, and constitutional. LC-FAOD were reported to have a significant impact on various aspects of patients' lives including physical functioning, participation in daily activities, emotional/psychological wellbeing, and social functioning. Lifestyle modifications (such as diet and exercise restrictions) were necessary because of the condition. Symptoms were typically episodic in presentation often arising or exacerbated during catabolic conditions such as prolonged exercise, fasting, physiological stress, and illness/infection. Symptoms were also commonly reported to lead to emergency room visits, hospitalization, and clinical complications. Conclusion: LC-FAOD have a considerable impact on patients' lives. There is a high degree of concordance in the signs, symptoms, and impacts of LC-FAOD reported by patients, caregivers, and clinicians; however, there were many symptoms and impacts that were only reported by patients and caregivers, thus demonstrating that insights from patient/caregiver experience data are integral for informing medical product development and facilitating patient-centered care.